2022
DOI: 10.4103/jpgm.jpgm_461_21
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean scar ectopic pregnancy masquerading as gestational trophoblastic disease

Abstract: Cesarean scar ectopic pregnancy (CSEP) is a very rare form of ectopic pregnancy in which implantation occurs at the site of the previous cesarean scar with low or absent beta-human chorionic gonadotropin (hCG) levels. It has various differential diagnoses on gross and microscopic examination. A delay in the identification and management of this condition may lead to life-threatening complications. Here, we discuss the incidence and clinicopathological features of chronic CSEP, its types, and differential diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Thus, although hysteroscopic removal is used as an effective treatment, CSPs may occasionally be associated with complications due to continuous growth of the retained tissue ( 8 ). It was reported that 3.3% of GTNs are located in cesarean scars ( 9 ), with rare case reports on choriocarcinomas, PSTTs and ETTs and a high rate of misdiagnosis ( 10 ). Indeed, it is crucial but challenging to make an acute diagnosis of GTN and tumor-like lesions by histology ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, although hysteroscopic removal is used as an effective treatment, CSPs may occasionally be associated with complications due to continuous growth of the retained tissue ( 8 ). It was reported that 3.3% of GTNs are located in cesarean scars ( 9 ), with rare case reports on choriocarcinomas, PSTTs and ETTs and a high rate of misdiagnosis ( 10 ). Indeed, it is crucial but challenging to make an acute diagnosis of GTN and tumor-like lesions by histology ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 3.3% of GTNs are located in cesarean scars ( 9 ), with rare case reports on choriocarcinomas, PSTTs and ETTs and a high rate of misdiagnosis ( 10 ). Indeed, it is crucial but challenging to make an acute diagnosis of GTN and tumor-like lesions by histology ( 10 ). For CSP choriocarcinoma, misdiagnosis can result in delayed treatment or even tumor metastasis ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these pregnancies can occur on myomectomy scars [1] . The displacement of the embryo in CSP is thought to be caused by either a fistula inside the scar tissue or a structural defect in the lower part of the uterus [2] . As women with CSP are more likely to experience uterine rupture, bleeding, hysterectomy, and loss of fertility, an early and precise diagnosis is essential.…”
Section: Introductionmentioning
confidence: 99%